Strengthening Farmer Resilience for Coconut Business Sustainability: Evidence from Aceh Besar - Henny Sulistyorini; Sumardjo Sumardjo; Anna Fatchiya; Ninuk Purnaningsih; Destika Cahyana (Jurnal Ilmiah Peuradeun, 2026)
Coconut is an important commodity for people in Aceh Besar, serving as a source of food, income, industrial raw materials, and coastal conservation. However, its sustainability is vulnerable to strategic environmental changes such as declining cultivation areas and productivity, limited acces to technology, insufficient role of farmer organizations, limited extension services, and pest attacks. Allegedly, the sustainability of the coconut business is affected by the level of farmers’ resilience, which underlies the development of farmer autonomy, enabling them to sustain their businesses in the long term. This research aims to analyze the factors that affect farmers’ resilience, autonomy, and the sustainability of their coconut businesses, and to examine the interrelationships among these variables. The research was conducted through a survey involving 106 coconut farmers in June-July 2024. The data were analyzed descriptively and inferentially using the SEM PLS method. The results show that farmers exhibit low levels of resilience, autonomy, and business sustainability. Both farmer resilience and autonomy show a direct positive effect on business sustainability. Resilience is affected by farmer characteristics, the role of extension workers, and social capital. Farmer autonomy is affected by farmer characteristics. Developing sustainable coconut businesses is achieved by enhancing farmers’ motivation, tailoring extension media to their needs, and strengthening their social networks.